Environmental chemistry applied to High School through laboratory experiments - Mainier , Renata Jogaib; Mainier , Fernando B. (Seven Editora, 2024)
The educational process must be attentive and be an agent that brings together the moments and changes that are occurring in the world, aiming at the present and future of man, as it is essential that human beings know and understand the functioning of the main industrial processes that are relate, directly or indirectly, with nature in the face of countless technological accidents that have left traces of destruction across the globe. Consequently, knowledge of Environmental Chemistry in secondary school must be one of the formal vectors of transformation at the teaching level, aiming and encouraging the formation of critical awareness in the processes in which chemical and related technologies can influence levels of environmental contamination. The purpose of this work consists of developing a learning process based on the construction of didactic models, whether using specific equipment or even using certain everyday objects, with the intention of creating in experiments the necessary and fundamental conditions for knowledge of Environmental Chemistry is both critical and systemic. To exemplify the teaching program, two themes were selected: the deterioration of batteries in the environment and the pollution and destruction of monuments and urban furniture. Based on these themes, laboratory experiments were developed to demonstrate how such products contaminate the environment. It is believed that the way of thinking in Environmental Chemistry, associating the fundamental concepts of Chemistry with the parameters that make up an environmental system, are closely linked to “feeling” or imagining the observed facts, natural or induced, that flow from the experiment. DOI:https://doi.org/10.56238/sevened2024.009-035